The Role of American Literature in the World Literature - Zokirova, Dilsora (European Journal of Life Safety and Stability (2660-9630), 2023)
Some of the earliest forms of American literature were pamphlets and writing extolling the benefits of the colonies to both a European and colonist audience. The revolutionary period also contained political writings, including those by colonists Samuel Adams, Josiah Quincy, John Dickinson, and Joseph Galloway, a loyalist to the crown. Two key figures were Benjamin Franklin are esteemed works with their wit and influence toward the formation of a budding American identity. Paine’s pamphlet Common Sense and Tge American Crisis writings are seen as playing a key role in influencing the political tone of the period.